Applications of QCD sum rules at finite temperature - Zhang, Yingwen (Department of Physics, 2019)
QCD Sum Rules is one of the most successful quantum field theory frameworks to extract hadronic information from QCD analytically. This technique is based on the Operator Product Expansion (OPE) and Cauchy's Theorem in the complex energy plane. OPE factorizes the short and long distance interactions where the former are calculated using perturbative theory, and the latter are parameterized in terms of the quark and gluon vacuum condensates. By using Cauchy's theorem, the results from QCD calculations can be matched to the hadronic channel, this is known as 'quark-hadron duality'. My Project involves using QCD Sum Rules to determine the behaviour of hadronic parameters of charmonium in the scalar and pseudoscalar channel and also light-light quark mesons in the vector and axial-vector channel at finite temperature. From our results of the behaviour of the width and the hadronic coupling at finite temperature, both channels of charmonium shows signs of survival beyond the deconfinement temperature Tc whereas the light-light quark mesons disappears at Tc. An extension of the method to finite density in. the axial-vector channel of light-light quark mesons also shows signs of disappearance at the deconfinement density μc.